Assessing the potential of oil palm frond juice as animal feed supplements by determining its nutrients, lignocellulosic and sugar contents - Nor Dini Rusli; Khairiyah Mat; Hasnita Che Harun; Wan Zahari Mohamed; Azhar Kasim; Mohd Zamri Saad; Hasliza Abu Hassim
Oil palm frond (OPF) juice has a great potential to be utilised as a supplement or main ingredients in animal feed. indeed, physical treatment by simply pressing the OPF petiole to obtain OPF juice is considered to be a promising technique because of its ability to loosen up the lig-nocellulose structure and release high amount of sugars, which further improve the degradability of OPF. This study attempts to characterise OPF juice by detennining its proximate composition, lignocellulosic contents and sugar contents for two different parts of OPF (whole OPF; 15.39% wt/wt and petiole; 18% wt/wt). Chemical composition of fresh OPF and OPF pressed ﬁbre were also analysed. The contents of crude protein, crude ﬁbre, ash, crude fat of OPF juice from petiole are not statistically different with OPF juice from whole OPF. Hemicellulose(HC) and cellulose(CE) were signiﬁcantly different between whole fresh OPF (21.06±0.83%HC; 31.27±0.72%CE), OPF pressed ﬁbre (9.03±0.40%HC; 45.32±1.35%CE) and OPF juice (0.72±0.02%HC; O.33±0.04%CE). Lignin content was signiﬁcantly highest in fresh OPF followed by pressed OPF and least in OPF juice. The improving of lignin degradation would increase digestibility and intake of the animal. For composition of free sugars in OPF juice was 60%(glucose), 18.5%(fructose) and 21%(sucrose). This OPF juice was found comparable to other feedstuff, which indicated a good prospective for animal feed.